2010
DOI: 10.1136/ard.2010.135525
|View full text |Cite
|
Sign up to set email alerts
|

Global effects of fluvastatin on the prothrombotic status of patients with antiphospholipid syndrome

Abstract: The data from this study support the belief that fluvastatin has multiple profound effects in monocyte activity, which might contribute to thrombosis prevention in APS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 35 publications
0
44
0
3
Order By: Relevance
“…Likewise, in systemic lupus erythematosus (SLE), MetS was found to be associated with other traditional risk factors for coronary heart disease, mainly obesity and LDL cholesterol Ͼ100 mg/dl (34), reinforcing the idea of risk factor clustering in autoimmune diseases. Of note, one-fourth of our patients were taking statins, a drug with known antiinflammatory, anticoagulant, and immunoregulatory effects (35). Its possible contribution to thrombosis prevention in our APS patients deserves further studies, since statins have multiple profound effects in monocyte activity by a significant inhibition on the protein expression of tissue factor (35).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Likewise, in systemic lupus erythematosus (SLE), MetS was found to be associated with other traditional risk factors for coronary heart disease, mainly obesity and LDL cholesterol Ͼ100 mg/dl (34), reinforcing the idea of risk factor clustering in autoimmune diseases. Of note, one-fourth of our patients were taking statins, a drug with known antiinflammatory, anticoagulant, and immunoregulatory effects (35). Its possible contribution to thrombosis prevention in our APS patients deserves further studies, since statins have multiple profound effects in monocyte activity by a significant inhibition on the protein expression of tissue factor (35).…”
Section: Discussionmentioning
confidence: 91%
“…Of note, one-fourth of our patients were taking statins, a drug with known antiinflammatory, anticoagulant, and immunoregulatory effects (35). Its possible contribution to thrombosis prevention in our APS patients deserves further studies, since statins have multiple profound effects in monocyte activity by a significant inhibition on the protein expression of tissue factor (35).…”
Section: Discussionmentioning
confidence: 91%
“…Very recently, proteomic study of monocytes and endothelial cells in patients with APS who received fluvastatin for one month, confirmed a significant reduction in the expression of TF, PAR-1, 2 and VEGF, which is associated with inhibition of the p38MAPK and NF-kB pathway [ 66 ]. Furthermore, Shoenfeld et al, based on the immunoregulatory and possibly antithrombotic effect of vitamin D, studied the serum levels of vitamin in patients with APS and its in vitro effects in HUVEC.…”
Section: Clinical and Laboratory Characteristicsmentioning
confidence: 94%
“…Given their positive effects on the immune system, on the vascular endothelium and on PONa (reviewed in [73]), statins may be suitable candidates within the context of a clinical trial. Indeed, an in vitro study showed that pravastatin was effecting at reverting the pro-adhesive and pro-thrombotic phenotype induced by aPL on endothelial cells, and a one month interventional trial with fluvastatin restored monocyte function in patients with APS [74,75]. Probucol ameliorated coagulation activation and lipid peroxidation in PAPS [76].…”
Section: Management Of Paps Related Atherosclerosismentioning
confidence: 99%